Kemampuan Komunikasi Digital Paul Gilster Pada Penerapan Pola Asuh di Kota Surakarta - Lestari, Eni; Sudarmaji, Sudarmaji (PRoMEDIA, 2024)
AbstractCommunication skills are the most basic skills in all aspects of life. The development of digital technology must be balanced with the ability of parents in social media for the implementation of appropriate parenting patterns. This study aims to determine how the influence of digital communication skills of parents, especially mothers, on the implementation of appropriate parenting patterns using Hurlock's parenting theory which is associated with Paul Gilster's digital literacy theory. This research method is descriptive qualitative, with objects of mothers in the Pajang sub-district environment. Data were obtained from interviews and observations. The results of the study stated that mothers who have high digital communication skills from the aspects of Internet Searching, Hypertextual Navigation, Content Evaluation, knowledge Assembly are able to implement appropriate authoritative parenting so that it has a positive impact on child development.Keywords: Digital Communication, Parenting, Parents               AbstraksiKemampuan berkomunikasi merupakan skill paling dasar dalam semua aspek kehidupan. Perkembangan teknologi digital wajib diimbangi dengan kemampuan orang tua dalam bermedia sosial untuk penerapan pola asuh yang sesuai. Penelitian ini bertujuan mengetahui bagaimana pengaruh kemampuan komunikasi digital orang tua terutama ibu terhadap penerapan pola asuh yang tepat dengan menggunakan teori pola asuh Hurlock yang dikaitkan dengan teori literasi digital Paul Gilster. Metode penelitian ini deskriptif kualitatif, dengan objek ibu di lingkungan kelurahan pajang. Data diperoleh dari hasil wawancara dan observasi. Hasil penelitian bahwa ibu yang memiliki kemampuan komunikasi digital yang tinggi dari aspek Internet Searching, Hypertextual Navigation, Content Evaluation, knowledge Assembly mampu menerapkan authotitative parenting yang tepat sehingga membawa dampak yang positif terhadap perkembangan anak.Kata Kunci: Komunikasi Digital, Pola Asuh, Orang Tua